Expression Conditions of Melanogenic Enzymes and Immune Molecular Markers in Atlantic Salmon Muscle During Different Productive Stages - Raúl Cortés; Cristián A. Valenzuela; Andrés Johnson; Ariel Valenzuela; Juan Antonio Valdés; Sebastián Escobar-Aguirre (Fishes)
Melanosis, or melanized focal changes (MFCs), is a significant issue in the Atlantic salmon (Salmo salar) farming industry, causing economic losses due to fillet downgrading. Nevertheless, molecular mechanisms underlying melanosis remain poorly understood, particularly in Chilean aquaculture. This study aimed to characterize transcriptional regulation associated with melanogenesis and inflammation in salmon muscle tissues exhibiting melanosis. Samples were collected from fish at three productive stages, all with MFCs in muscle in common: freshwater at two different origins and accumulated thermal units “ATUs” (300 ATUs post-antibiotic overdose, “Security”; 600 ATUs post-vaccination, “Vaccination”) and seawater harvest (“Harvest”). Gene expression analysis by qPCR targeted melanogenesis-related genes (mitf, tyr, and dct) and immune markers (arg2, inos2, and il-1β). Results revealed significant transcriptional modulation in freshwater samples, including downregulation of mitf, upregulation of dct, and changes in immune-related genes (arg2 and inos2). In contrast, seawater (“Harvest”) samples showed significant upregulation of tyr and dct, but no significant immune gene modulation. These findings indicate distinct molecular responses depending on the MFCs’ development stage, emphasizing early stages as critical points for intervention. Unlike recent studies, which have predominantly focused on samples from the harvest stage, this work uniquely integrates results from both the freshwater phase and the harvest stage.